2021
DOI: 10.3390/ijms22083860
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Reshaping and Neuronal Outcomes in the Temporal Lobe Epilepsy

Abstract: Temporal lobe epilepsy (TLE) is one of the most common types of focal epilepsy, characterized by recurrent spontaneous seizures originating in the temporal lobe(s), with mesial TLE (mTLE) as the worst form of TLE, often associated with hippocampal sclerosis. Abnormal epileptiform discharges are the result, among others, of altered cell-to-cell communication in both chemical and electrical transmissions. Current knowledge about the neurobiology of TLE in human patients emerges from pathological studies of biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 172 publications
(146 reference statements)
5
14
0
Order By: Relevance
“…We found that Mir155hg knockdown inhibited the abnormal discharge and markedly decreased EEG power in SE rats. It is widely accepted that generalized epileptiform discharges contribute to abnormal synaptic connections and neural circuitry [50,51]. A strong relationship between long-lasting epileptic discharges and cognitive impairment of SE also has been reported in much literature [30,52].…”
Section: Discussionmentioning
confidence: 98%
“…We found that Mir155hg knockdown inhibited the abnormal discharge and markedly decreased EEG power in SE rats. It is widely accepted that generalized epileptiform discharges contribute to abnormal synaptic connections and neural circuitry [50,51]. A strong relationship between long-lasting epileptic discharges and cognitive impairment of SE also has been reported in much literature [30,52].…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that emotions occur in specific regions of several parts of the cerebral cortex, such as the amygdala, ventral striatum, putamen, caudate nucleus, and ventral tegmental area ( 46 ). TLE is more common in limbic system involvement, suggesting that children with TLE may be more prone to mood disorders ( 8 , 47 49 ). In this study, The results were found in the open-field experiment that the retention time in the central region of rats in the EP group was delayed compared with that in rats in the control group, the locomotor distance traveled in the central region was prolonged, the total distance was prolonged, and the average speed was increased.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy affects more than 70 million people worldwide ( 3 ), 60% of which experience childhood onset ( 4 ). In children with epilepsy, 10–30% have temporal lobe epilepsy (TLE) involving the hippocampus, amygdala, entorhinal cortex and other limbic system structures, some of which easily develop refractory epilepsy or persistent epilepsy, resulting in varying degrees of learning and memory impairment ( 5 ), cognitive dysfunction ( 6 ), and mood disorders ( 7 , 8 ). However, reducing brain injury and emotional and behavioral disorders that develop after the onset of epilepsy has become a problem requiring close attention and considerable effort from pediatricians to find a solution ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a change in the number of NT receptors during epileptic seizures should also be considered. In patients with temporal lobe epilepsy (TLE), a general increase in glutamatergic receptors (α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and N-methyl-D-aspartate (NMDA) receptors, kainic and metabotropic receptors), along with a general decrease in GABAergic ionotropic receptors (GABA A , GABA B ) causes disruption in EIB [ 55 ]. Alterations in different receptors of monoamine NTs are also found in epilepsy [ 39 ].…”
Section: Scfa In Seizure Controlmentioning
confidence: 99%